2015
DOI: 10.2105/ajph.2014.302431
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Hazard and Survival After Tuberculosis Treatment

Abstract: Objectives We compared mortality among tuberculosis (TB) survivors and a similar population. Methods We used local health authority records from3 US sites to identify 3853 persons who completed adequate treatment of TB and 7282 individuals diagnosed with latent TB infection 1993 to 2002. We then retrospectively observed mortality after 6 to 16 years of observation. We ascertained vital status as of December 31, 2008, using the Centers for Disease Control and Prevention’s National Death Index. We analyzed mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 24 publications
(18 reference statements)
1
42
0
1
Order By: Relevance
“…1 Asthma and coexistent TB predispose to clinical manifestations, including pneumonia, bronchiectasis and pulmonary abscesses. 3,5 We report here the first case from India.…”
Section: Dual Infection With Pulmonary Tuberculosis and Lophomonas Blmentioning
confidence: 81%
See 2 more Smart Citations
“…1 Asthma and coexistent TB predispose to clinical manifestations, including pneumonia, bronchiectasis and pulmonary abscesses. 3,5 We report here the first case from India.…”
Section: Dual Infection With Pulmonary Tuberculosis and Lophomonas Blmentioning
confidence: 81%
“…3 We have found health outcomes for populations with either a history of active TB or LTBI to be consistently dissimilar to those of the general US population in our other analyses as well. 4,5 We are confident that our adjusted model reliably captures the burden of excess mortality associated with a history of fully treated TB in the US. More importantly, we believe that research to identify and explain causal factors related to this phenomenon may lead to strategies that can reduce this burden.…”
Section: In Replymentioning
confidence: 82%
See 1 more Smart Citation
“…As well as being the most common clinical form, it is also the most relevant, as this is a transmittable form of the disease. A study found that individuals with the pulmonary form had a longer survival period than those with the extrapulmonary form of the disease [30].…”
Section: Discussionmentioning
confidence: 99%
“…Although TB is less prevalent in the US than in many other countries, nearly 10,000 new TB cases are diagnosed in the US annually [ 2 4 ]. TB is a debilitating and potentially deadly illness with long-term health consequences and substantially increased mortality risk even after treatment is completed [ 5 , 6 ]. Further, TB in the US exacts great financial and societal costs [ 5 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%